Pendampingan Peningkatan Kualitas dan Kreativitas Penulisan Karya Ilmiah Bagi Mahasiswa Universitas Islam Zainul Hasan Probolinggo - Shobirin, Shobirin (Jurnal Solusi Masyarakat (JSM), 2024)
This research examines the effectiveness of academic writing mentoring for Arabic Language Education students at Zainul Hasan Islamic University (UNZAH) Genggong Probolinggo, with a focus on improving the quality and creativity of academic work. A qualitative method with a descriptive approach was used to collect data through observation, interviews, and documentation. The results show that structured and continuous mentoring has a significant positive impact on the quality and creativity of students' academic work. Students feel an improvement in their ability to formulate problems, gather data, analyze, and construct strong arguments. However, there are still challenges such as time and resource constraints, lack of motivation, and students' readiness in academic writing. This research recommends strategies to address these challenges, including the development of a more comprehensive mentoring program, structured writing training, and increased collaboration between faculty and students.